Sistem Kendali Arsip Kepegawaian (SIKASEP) Berbasis Desktop Pada Balai Sosial Bina Remaja (BSBR) Karya Mandiri - Moh Ali Albar; Hidayatul Akbar (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
This employee filing information system has several features, including managing curriculum vitae, employee leaves, salary increase, and rank, retired, and transfer. The data is still stored conventionally, making the data search process very long. This system is desktop based and uses the Java programming language. The results of the questionnaire showed that as many as 24 respondents stated that they agreed to 80% and as many as 6 respondents stated that they strongly agreed to 20% for the use of this application. Keywords: